Finkel, Irving: The Ark Before Noah. Decoding the Story of the Flood. London 2014 (Rezension) - Streck, Michael P. (2017)
Review too Irving Finkel: The Ark Before Noah. Decoding the Story of the Flood. London: Hodder & Stoughton, 2014. 352 S. 16,3 × 23,6 cm. ISBN 978-1-444-75705-7. Preis: £ 25,00.
info:eu-repo/semantics/openAccess
Keywords: Review; Ark; Noah